The Impact Of Paylater Online Loans On Society's Life Based On Islamic Views - Usman, Khairunnisa Pratiwi Maulida; Alifa Shaliha Tsabita; Suganda, Nurkalina Pratiwi; Momod Abdul Somad; A. N. Turginbayeva (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2024)
This research aims to determine the influence of debt or online loans on people's psychology along with five related suicide cases. The method used in this analysis is case study-based qualitative research. The results of this study show that there are five cases above that intersect on two things, namely debt and online loans and suicide due to depression or pressure. All those involved with usury will get a big sin. In addition, usury is also forbidden because it can have a negative impact both materially and inwardly; one of the impacts is excessive pressure that raises the tendency to commit suicide